2000
DOI: 10.1007/s11908-000-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system toxoplasmosis in HIV pathogenesis, diagnosis, and therapy

Abstract: In patients with HIV, Toxoplasma gondii is the most frequent infectious cause of focal brain lesions. Particularly in advanced HIV disease, it can cause significant morbidity and mortality. Current clinical practice involves empiric therapy with pyrimethamine and sulfadiazine, upon a presumptive diagnosis of toxoplasmic encephalitis, based on serologic, clinical, and radiological features. This approach continues to evolve, as new diagnostic strategies, such as the use of immunoglobulin G antibody titers and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 34 publications
0
28
0
6
Order By: Relevance
“…Earlier studies showed that different levels of anti-T. gondii IgG antibodies were unable to determine a reactivation or to follow the course of cerebral toxoplasmosis (26,27,34). However, others have suggested that high titers in patients might be indicative of the presence of cerebral toxoplasmosis or a higher risk of developing the disease (13,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies showed that different levels of anti-T. gondii IgG antibodies were unable to determine a reactivation or to follow the course of cerebral toxoplasmosis (26,27,34). However, others have suggested that high titers in patients might be indicative of the presence of cerebral toxoplasmosis or a higher risk of developing the disease (13,18).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral toxoplasmosis is one of the most common opportunistic neurological infections in AIDS patients, and it is typically observed in the later stages of human immunodeficiency virus (HIV) infection (26). It is also directly related to the prevalence of anti-T. gondii antibodies in the general population (21).…”
mentioning
confidence: 99%
“…3 Cerebral toxoplasmosis is typically observed in the later stages of HIV infection. 4,5,6 CNS disease occurs when, CD4 counts are <200 cells/μL. The greatest risk is in patients with CD4 counts <50 cells/μL.…”
mentioning
confidence: 99%
“…In patients infected with human immunodeficiency virus (HIV), more than 95% of Toxoplasma encephalitis cases involve reactivation of a latent infection [2]. Contrary to the situation in adults, toxoplasmosis of the central nervous system is not a common opportunistic infection in children infected with HIV.…”
mentioning
confidence: 99%